Liquidity Preference and Risk Aversion with an Exponential Utility Function: Comment - Bierwag, G. O. (Review of Economic Studies, 1974)
Journal Article Liquidity Preference and Risk Aversion with an Exponential Utility Function: Comment Get access G. O. Bierwag G. O. Bierwag University of Oregon Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 2, April 1974, Pages 301–302, https://doi.org/10.2307/2296720 Published: 01 April 1974